ETHNOMATHEMATICS: MATHEMATICAL MEANINGS AND CONCEPTS CONTAINED IN BANTEN BATIK PATTERNS - Umi Kulsum; Lilik Amalia; Indah Lestari; Roliyah Roliyah; Jaka Wijaya Kusuma (International Journal of Economy, Education and Entrepreneurship, 2022)
Ethnomathematics utilizes numerical ideas in a culture that individuals in everyday life use. Indonesia is a country rich in ethnic and social practices. Batik Banten is one of the Indonesian nation's colonial heritage, which originates from Banten. Batik Banten has 75 typical Banten decorations applied to 54 batik patterns. This research was conducted to determine the meaning of Banten batik patterns or motifs and understand the numerical ideas in Banten batiks motifs. This research includes personal exploration with ethnographic methodology because what is being researched is about culture. The results showed that the Banten batik motifs, in addition to having a philosophical meaning in each pattern/motif, the motifs in Banten batik also contain numerical ideas or mathematical concepts such as geometric transformations, spatial structures, and so on